Mengatasi Kecemasan pada Pasien Hemodialisis dengan terapi Guided Imagery berbasis Spiritual di Rumah Sakit: Overcoming Anxiety in Hemodialysis Patients with therapy Spiritually based Guided Imagery in Hospitals - Yuwono, Trisno; Dian Ellina, Agusta (Chakra Brahmanda Lentera Institute, 2025)
Patients with chronic kidney failure often experience anxiety before undergoing hemodialysis therapy, presenting symptoms such as palpitations, nausea, tremors, and nervousness. Anxiety is triggered by factors such as seeing the blood tubing, treatment costs, invasive procedures, and uncertainty about recovery. This community service initiative aims to address anxiety in hemodialysis patients at Bhayangkara Kediri Hospital through spiritual-based Guided Imagery therapy, aimed at providing calmness and reducing stress associated with the treatment. The community service activity was conducted from September 2 to 13, 2024, at the Hemodialysis Unit of Bhayangkara Kediri Hospital. The program was carried out in three phases: preparation, implementation, and evaluation. A total of 14 patients participated in this activity. To measure the level of anxiety before and after the therapy, the Zung Self-Rating Anxiety Scale questionnaire was used, a common tool for assessing anxiety symptoms. The results of this initiative showed a significant reduction in anxiety levels in hemodialysis patients at Bhayangkara Kediri Hospital after receiving spiritual-based Guided Imagery therapy. The therapy effectively alleviated anxiety symptoms such as palpitations and other physical tension related to anxiety before the hemodialysis procedure. Spiritual-based Guided Imagery therapy was proven to be effective in reducing anxiety in hemodialysis patients. This program can serve as a beneficial non-pharmacological approach in managing patient anxiety in the hemodialysis unit.